The Initial Hyperglycemia in Acute Type II Pyrethroid Poisoning - Kim, Dongseob (The Korean Academy of Medical Sciences, 2015)
This retrospective observational case series study was conducted to describe the clinical feature of acute type II pyrethroid poisoning, and to investigate whether hyperglycemia at presentation can predict the outcome in patients with type II pyrethroid poisoning. This study included 104 type II pyrethroid poisoned patients. The complication rate and mortality rate was 26.9% and 2.9% in type II pyrethroid poisoned patients. The most common complication was respiratory failure followed by acidosis and hypotension. In non-diabetic type II pyrethroid poisoned patients, patients with complications showed a higher frequency of hyperglycemia, abnormalities on the initial X ray, depressed mentality, lower PaCO2 and HCO3- levels, and a higher WBC and AST levels at the time of admission compared to patients without complication. Hyperglycemia was an independent factor for predicting complications in non-diabetic patients. Diabetic patients had a significantly higher incidence of complications than non-diabetic patients. However, there was no significant predictive factor for complications in patients with diabetes mellitus probably because of small number of diabetes mellitus. In contrast to the relatively low toxicity of pyrethroids in mammals, type II pyrethroid poisoning is not a mild disease. Hyperglycemia at presentation may be useful to predict the critical complications in non-diabetic patients.